2019
DOI: 10.1016/j.virusres.2019.197673
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and antigenic diversity of African swine fever virus

Abstract: Highlights ASFV demonstrates extreme genetic diversity and use multiple mechanisms for acquisition novel phenotype characteristics  Evolutionary rate of ASFV variable regions may approach similar values to RNA viruses  More complete ASFV sequences are needed to better understand viral genome plasticity, antigenic diversity, and evolution  Heamdsorbtion inhibition assay is a reliable tool in defining ASFV antigenic diversity and candidate vaccine efficiency ABSTRACT African swine fever virus ( ASFV) is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 95 publications
1
42
0
3
Order By: Relevance
“…The protein pEP402R, a homologue of the T-lymphocyte surface antigen CD2, encoded by the EP402R gene is located in the lipoprotein membrane of the outer viral envelope and plays an important role in the adhesion of erythrocytes to infected cells (hemadsorption) and the binding of the ASFV particles to host erythrocytes during infection (Alejo et al 2018 ; Dixon et al 2019 ). This gene has been used to define eight viral antigenic types called serogroups (Malogolovkin and Kolbasov 2019 ). The results of the present study showed that the BUR/18/Rutana and MAL/19/Karonga ASFV strains may share the hemadsorption properties with ASFV strains belonging to serogroups 7 and 8, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protein pEP402R, a homologue of the T-lymphocyte surface antigen CD2, encoded by the EP402R gene is located in the lipoprotein membrane of the outer viral envelope and plays an important role in the adhesion of erythrocytes to infected cells (hemadsorption) and the binding of the ASFV particles to host erythrocytes during infection (Alejo et al 2018 ; Dixon et al 2019 ). This gene has been used to define eight viral antigenic types called serogroups (Malogolovkin and Kolbasov 2019 ). The results of the present study showed that the BUR/18/Rutana and MAL/19/Karonga ASFV strains may share the hemadsorption properties with ASFV strains belonging to serogroups 7 and 8, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a relatively low overall genomic mutation rate, the evolutionary rate of the ASFV variable regions seems to approach those of RNA viruses and can greatly affect ASFV genome structure [25,26]. ASFV strains showing MGFs gene duplication are often associated with a more violent phenotype while attenuating loss of MGFs occurs after viral passage in in vitro cell culture [22,26,27].…”
Section: Asfv Genome Structurementioning
confidence: 99%
“…Despite having a relatively low overall genomic mutation rate, the evolutionary rate of the ASFV variable regions seems to approach those of RNA viruses and can greatly affect ASFV genome structure [25,26]. ASFV strains showing MGFs gene duplication are often associated with a more violent phenotype while attenuating loss of MGFs occurs after viral passage in in vitro cell culture [22,26,27]. Comparative genomic analyses have also identified a range of genes in the constant region undergoing positive selection (e.g., CD2v/EP402R and C-type lectin/EP153R) that represent another source of genetic diversity among ASFV isolates [5,26,28].…”
Section: Asfv Genome Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the epidemic has a tendency to spread rapidly around the world (Zhou et al, 2018), so there is an urgent need for an effective method to control the spread of ASF. Although its pathogenesis and modes of transmission are known to some extent (Arias, Jurado, Gallardo, Fernández‐Pinero, & Sánchez‐Vizcaíno, 2018; Dixon, Sun, & Roberts, 2019), the effective ASF vaccine and medicine have not yet been developed, due to the complex structure of ASFV (Malogolovkin & Kolbasov, 2019; Sánchez, Pérez‐Núñez, & Revilla, 2019; Sánchez‐Cordón, Montoya, Reis, & Dixon, 2018; Sánchez‐Vizcaíno, Mur, & Martínez‐López, 2012; Sunwoo et al, 2019). Therefore, the detection of ASFV is essential for pork industry food safety and disease prevention and control worldwide.…”
Section: Introductionmentioning
confidence: 99%